The brink : an Awakened novel - Murray, James S. (James Stephen), 1976-; Wearmouth, Darren (Awakened novel, 2020)
"Former NYC Mayor Tom Cafferty has been haunted by memories of the hyper intelligent, bloodthirsty creatures that attacked his city. But the attack was not an isolated incident - now the creatures have spread worldwide. And a secret organization is holding nations hostage with the knowledge of how to kill them. Will Cafferty and his team be able to save the entire planet from an apocalyptic scale disaster?"--Publisher description.